2013
DOI: 10.1002/chem.201203328
|View full text |Cite
|
Sign up to set email alerts
|

Revealing Unexpected Mechanisms for Nucleophilic Attack on SS and SeSe Bridges

Abstract: The reactivity of disulfide and diselenide derivatives towards F(-) and CN(-) nucleophiles has been investigated by means of B3PW91/6-311+G(2df,p) calculations. This theoretical survey shows that these processes, in contrast with the generally accepted view of disulfide and diselenide linkages, do not always lead to SS or SeSe bond cleavage. In fact, SS or SeSe bond fission is the most favorable process only when the substituents attached to the S or the Se atoms are not very electronegative. Highly electr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 82 publications
0
16
0
Order By: Relevance
“…43,52 In more general terms, it should also be stressed that recent investigations of nucleophilic attacks on S-S bridges continue to reveal unexpected reaction mechanisms. 53 It is evident that putative reaction scenarios become even more intricate when mechanochemical activation comes into play. Indeed, external forces can activate new reactions channels, among which C-S or S-S bond rupture without the direct intervention of OH − are apparently the most plausible options.…”
mentioning
confidence: 99%
“…43,52 In more general terms, it should also be stressed that recent investigations of nucleophilic attacks on S-S bridges continue to reveal unexpected reaction mechanisms. 53 It is evident that putative reaction scenarios become even more intricate when mechanochemical activation comes into play. Indeed, external forces can activate new reactions channels, among which C-S or S-S bond rupture without the direct intervention of OH − are apparently the most plausible options.…”
mentioning
confidence: 99%
“…Another consideration is that the strength of the nucleophile is as much important as the leaving group ability. This topic has been rigorously investigated by Bachrach and co-workers [208] who investigated the mechanism of a series of nucleophilic substitution reactions involving different species as nucleophiles and leaving groups in methylsulfenyl derivatives (level of theory: B3LYP/augcc-pVDZ) and found in all cases an addition-elimination mechanism.…”
Section: Nucleophilic Attack Of a Thiol/thiolate Anion At Diselenidesmentioning
confidence: 99%
“…Finally, it is worth to mention also some analyses focused on the chalcogen-chalcogen bond nature, carried out on symmetric and asymmetric disulfides and diselenides of general formula R 1 XXR 2 (X = S, Se; R 1 , R 2 = CH 3 , OH, F, NH 2 ) [208]. Yanez, Boyd and co-workers investigated the nucleophilic attacks of Fand CNat the dichalcogenide substrates (level of theory: B3PW91/6-311+G(2df,p)).…”
Section: Nucleophilic Attack Of a Thiol/thiolate Anion At Diselenidesmentioning
confidence: 99%
“…This theoretical model has proven to be very reliable for the treatment of organoselenium compounds and recently was shown to be well suited for the description of disulfide and diselenide bridges, [42] using the coupled cluster CCSD(T) ab initio method as a reference. This theoretical model has proven to be very reliable for the treatment of organoselenium compounds and recently was shown to be well suited for the description of disulfide and diselenide bridges, [42] using the coupled cluster CCSD(T) ab initio method as a reference.…”
Section: Computational Detailsmentioning
confidence: 99%
“…[25][26][27][28] Consequently, the most powerful techniques in protein sequencing are based on the cleavage of SAS or SeASe bridges within the protein, but the mechanisms at the molecular level are far from being well understood. [42] Nucleophilic attacks or oxidation processes on disulfides and diselenides give rise to mixed SASe bridges [43][44][45] which are important in some biochemical processes. [31][32][33][34][35][36][37] In all cases, it was found that the SAS or the SeASe bond fission is the dominant process, although in the systems investigated the substituents attached to S or Se were either identical or ones of similar electronegativity.…”
Section: Introductionmentioning
confidence: 99%